PHARMACEUTICAL DEVELOPMENT OF A SCALP LOTION BASED ON CAPSICUM - Стрепко, Іванна; Гриновець, Ігор (SWorldJournal, 2025)
Excessive hair loss (alopecia) is a common aesthetic and medical issue that affects both men and women. It may be caused by various etiological factors such as stress, hormonal imbalances, inadequate nutrition, or improper hair care. One of the well-known